(untitled)
Gender problems in Islam, inter-religious unity in approach to relations between man and woman are discussed. Analysis of woman status in the family, in the context of limitation of her rights in relation to religious orientation of the society is presented. // o;o++)t+=e.charCodeAt(o).toString(16);return t